Effect of surface modification on the hot corrosion resistance of Inconel 718 at 700 °c - Kumar S.; Satapathy B.; Pradhan D.; Mahobia G.S. (My University, 2025)
In the present paper surface of superalloy Inconel 718 was modified by aluminizing and ultrasonic shot peening process (USSP). Pack aluminizing produced uniform nickel aluminide layer of ∼280 μm with outwardly grown NiAl layer of ∼76 μm on the surface of the superalloy. Ultrasonic shot peening with 3 mm shots for 5 min duration created a nanostructure layer upto a depth of ∼85 μm on the alloy surface. Modified alloy was exposed to two different salt environments (NaCl 100 wt% and Na2SO4(75 wt%)+NaCl(15 wt%)+V2O5(10 wt%)) in two zone split type tube furnace at 700 °C. Aluminized, USSPed, and the hot corroded samples were examined using X-ray diffraction and SEM/EDS techniques. NaCl(100 wt%) environment observed to be more damaging in comparison to the salt mixture. The aluminized surface reduced the hot corrosion by 50% whereas USSPed sample showed two times more corrosion as compared to the untreated alloy. Increase in surface activity of the alloying elements after ultrasonic shot peening treatment was found to be responsible for high rate of corrosion in USSPed samples whereas in aluminized sample formation of uniform alumina layer acted as a barrier for the diffusion of corrosive species into the surface. © 2019 IOP Publishing Ltd.